(untitled) (Eurasian Journal of Humanities and Social Sciences, 2025)
The article reflects the psychophysiological foundations of human speech activity, the psychological foundations of oral speech and the scientific opinions of scientists on this subject, the ideas about the acquisition of paradigmatic and syntagmatic relations of the grammatical system of speech.